School Principal's Management Style And Teachers' Work Motivation - Stepanyan, Narine; Geghamyan, Elen (Զանգակ հրատ.)
The effectiveness of the school system largely depends on the principal’s management style and its impact on teachers' work motivation. With the rapid changes in the educational sphere, school leaders must adapt their leadership approaches to maintain teachers' engagement, job satisfaction, and motivation. This study investigates the relationship between school principals’ management styles and teachers’ motivation, highlighting how various styles—authoritarian, democratic, and liberal—influence the level of motivation among teachers. The research was conducted across four schools in Armenia, utilizing quantitative and qualitative methods, including surveys and interviews. The findings indicate that teachers under democratic leadership exhibit higher creative motivation, while those under authoritarian leadership show lower intrinsic motivation but stronger compliance. The study contributes to the understanding of educational leadership psychology and provides practical recommendations for school management. This study empirically examines the correlation between school principals’ leadership styles and teachers’ work motivation, providing statistical validation of this relationship. Unlike predominantly theoretical studies, it integrates psychological assessment tools to ensure systematic analysis. The findings highlight leadership-motivation patterns and propose a hybrid leadership model for optimizing teacher engagement and job satisfaction.
Keywords: Education